Solidaritas Digital "Brave Pink Hero Green" Di Instagram: Analisis Wacana Kritis Model Fairclough - Afthoniya Nurin Nadhifa; Sri Yanuarsih; I Wayan Letreng (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
The phenomenon of digital solidarity on Instagram from late August to early September 2025 reflected the transformation of the discourse of resistance and collective consciousness in the virtual public space. This study aims to analyze the construction of meaning, the processes of production, and socio-cultural context of the digital solidarity discourse that developed during that period. The method used is descriptive qualitative with a Critical Discourse Analysis approach modeled after Norman Fairclough, which encompasses the dimensions of text, discourse practice, and socio-cultural practice. The research data consists of five Instagram posts representing the use of slogans, color symbols, and reflective narratives. The results show that the discourse was constructed through linguistic and semiotic strategies that emphasize empathy, moral courage, and collective solidarity. At the level of discourse practice, production and distribution are collaborative and participatory. Socio-culturally, this discourse marks a shift in resistance towards non-confrontational cultural practices oriented towards collective moral consciousness in the landscape of digital capitalism.